The Impact of Changing Gender Roles on the Dynamics of Family Law in the Modern Era - Muhammad Husni Abdulah Pakarti; Edy Saputra; Husain; Lexy Fatharany Kurniawan; Nahdia Nazmi (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2024)
The role of gender in society has undergone significant changes in recent decades. Social transformation, economic advancements, and the increasing advocacy for gender equality have influenced the dynamics of family law. This research aims to analyze the impact of changing gender roles on family law dynamics in the context of the modern era. In this case study, the researcher will examine how changes in gender roles affect child custody, roles in marriage and divorce, and other legal implications using a qualitative approach by collecting data from various sources, such as literature reviews, documentation, and analysis of related legal cases. Data analysis will be conducted using a comparative descriptive approach to identify changes occurring in family law and its relation to changing gender roles. The results of this study indicate that changes in gender roles within family law have significant impacts in the modern era. These changes include the expected roles of husbands and wives in marriage, child custody after divorce, as well as legal protection against gender discrimination and access to fair legal services. Although challenges still exist, it is important for society and the legal system to support these changes and address existing barriers. Thus, marital and divorce relationships can become more balanced, fair, and consider the best interests of the couples and children involved.